El Excentrico, 1976-10-05 - Garcia, Humberto:::Publisher:::::::::::: (San Jose, CA; Garcia Printing, 2024)
October 5, 1976 [5 de octubre de 1976]. Ano 27, No 12. Cover has a photo of politician Luis G. Juarez, smiling towards a crowd. The headline reads, "Discussion with Luis G. Juarez."